Saturation of the magnetorotational instability and the origin of magnetically elevated accretion discs. Issue 4 (27th March 2023) - Begelman, Mitchell C; Armitage, Philip J
ABSTRACT: We propose that the strength of angular momentum transport in accretion discs threaded by net vertical magnetic field is determined by a self-regulation mechanism: the magnetorotational instability (MRI) grows until its own turbulent resistivity damps the fastest growing mode on the scale of the disc thickness. Given weak assumptions as to the structure of MRI-derived turbulence, supported by prior simulation evidence, the proposed mechanism reproduces the known scaling of the viscous α-parameter, $α \propto β _z^{-1/2}$ . Here, $β _z = 8π p_{\rm g}/B_{z0}^2$ is the initial plasma β-parameter on the disc mid-plane, B z 0 is the net field, and p g is the mid-plane gas pressure. We generalize the argument to discs with strong suprathermal toroidal magnetic fields, where the MRI growth rate is modified from the weak-field limit. Additional sources of turbulence are required if such discs are to become magnetically elevated, with the increased scale heights near the mid-plane that are seen in simulations. We speculate that tearing modes, associated with current sheets broadened by the effective resistivity, are a possible source of enhanced turbulence in elevated discs.